PENGARUH VARIABEL EKONOMI MAKRO TERHADAP PEMBIAYAAN PERBANKAN SYARIAH PERIODE 2010-2018 - Mirza Zulfikar Hisbul Rachman; Mintarti Ariani; Eko Suwardyono (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2020)
This study aims to identify the effect of remittances on economic growth. The objects used in this study are five ASEAN countries, namely Indonesia, Cambodia, the Philippines, Vietnam, and Thailand, for the period 2005 to 2016. There are other variables, namely gross fixed capital formation, household consumption expenditure, trade, and population growth which are used as control variable in this model. This study uses a quantitative approach and panel data methods. As a result, there are significant and negative effects on remittances: significant and positive effects on gross fixed capital formation, significant and positive effects on household consumption expenditures, significant and positive effects on trade, and significant and negative effects on population growth on economic growth in five countries. ASEAN.